PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR METEMATIKA PESERTA DIDIK KELAS V SD NEGERI 65 PRTANI TP. 2013/2014 - Rahmi Juli Juli; Susda Heleni Heleni; Syarifah Nur Siregar Nur Siregar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study aims to improve the learning process and improve learning outcomes class V learners of SD Negeri 65 Petani by applying cooperative learning model STAD . The subjects were learners in class V which consisted of 12 women and 12 men with heterogeneous academic ability. This research is a class act with two cycles . Each cycle has four stage : planning , implementation , observation and reflection . Data collection instrument in this study is the observation sheet activities teachers and learners , as well as the achievement test. Sheets were analyzed qualitatively descriptive narrative, while the achievement test were analyzed by descriptive statistical study by analyzing the development of the individual and group values ​​, KKM achievement analysis , and analysis of the success of the action. Results of research on the observation sheet shows the activity of teachers and learners have done well and according to plan after the action . Improvements in the learning process of students and increase the number of learners who achieve KKM at the end of each cycle UH compared to the number of learners who achieve a score of KKM on base score. At the base score only 25% of learners who reach KKM , the UH I increased to 62.5% and the UH II also increased to 79.2% . The results of this study indicate that the application of cooperative learning model STAD can improve the learning process and improve learning outcomes class V learners of SD Negeri 65 Petani in the second semester of the academic year 2013/2014 . Keywords: Mathematics Learning Outcomes, Cooperative Learning, Student Teams Achievement Division (STAD), Classroom Action Research .